Tradisi Beati di Kabupaten Gorontalo Utara : (Studi Etnografi terhadap Prosesi dan Makna Verbal Tuja'i ) - Ibnu Rawandhy N. Hula; Ana Mariana (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This paper focuses on the stages of implementing the beati tradition in North Gorontalo District communities and explains the content of the verbal meaning of tuja'i. The research method used is descriptive-analytic research with an ethnographic study approach. This paper aims to analyze the cultural elements in the tradition of the procession, manner and behavior, and verbal language. This study found that the poetic verbal meaning of tuja'i contains directions, praise, advice, and advice, leading a girl to become a complete Muslim by a) pledging to carry out religious orders on al-arkan al-tsalatsah, as well as customary rules based on sharia b) obeying parents, making them happy and maintaining the right name of the family, c) maintaining the purity of oneself both physically and mentally which is marked by noble morals d) Avoiding lousy temperament.